Analisis Kompetensi Sosial dan Kompetensi Kepribadian Pendidik pada Sekolah Luar Biasa - Lasari, Desy Murni (An-Nadwah, 2023)
The lack of undergraduate education backgrounds among some special school teachers has an impact on the competences that educators must possess, which is the driving force behind this study. The aim of this study is to describe the social competency of special education teachers in Central Aceh District. To find out the description of the personality competencies of educators in special schools in Central Aceh District. The approach to this study used qualitative research with descriptive methods by giving questions in the form of interviews to teachers in special schools as many as 5 informants The results of this study show that the teacher's social competency picture can be seen from the teacher communicating well with students and also having good socialization not only in the school environment but outside of school, teachers are also objective towards all children and do not discriminate between children both in terms of economics and background. In addition, the relationship between teachers and parents and the community is also good. Thus the social competence of the teacher can be said to be good. Furthermore, demonstrating personality competence at Special Schools in Central Aceh District is very well seen from actions that are in accordance with both legal and religious norms, being honest teachers and being role models for their students, showing enthusiasm at work and being responsible for their work.